THE JOINT EFFECT OF BORROWER TARGETED MACROPRUDENTIAL INSTRUMENTS AND CAPITAL REGULATIONS ON PROCYCLICALITY OF LOAN-LOSS PROVISIONS - Olszak, Małgorzata; Roszkowska, Sylwia; Kowalska, Iwona (Copernican Journal of Finance & Accounting, 2019)
We analyze the effects of macroprudential policy and micro-prudential capital regulations on the procyclicality of loan-loss provisions, using individual bank information from over 65 countries. In this study we test whether the interaction between borrower targeted macroprudential policy instruments and restrictive micro-prudential capital regulations tends to adjust the countercyclical effect of borrower targeted instruments and capital regulations. To this end we apply the two-step GMM estimator with robust standards errors. Our analysis implies that merging restrictive borrower targeted instruments and capital regulations tends to weaken the countercyclical effect of borrower targeted macroprudential policy instruments and restrictive capital adequacy regulations. This effect depends on size, and is stronger in large banks.